Myocarditis with Advanced Atrioventricular Block after Allogeneic Stem Cell Transplantation: A Case Report and Literature Review - Sumi, Masahiko; Kitahara, Mari; Shishido, Tsutomu; Kazumoto, Hiroko; Uematsu, Nozomu; Kirihara, Takehiko; Sato, Keijiro; Ueki, Toshimitsu; Hiroshima, Yuki; Shimizu, Kunihiko; Kobayashi, Hikaru (Internal Medicine, 2020)
A 51-year-old woman with Philadelphia chromosome-positive acute lymphoblastic leukemia underwent a second cord blood transplantation followed by maintenance therapy with interferon-α. After 33 months, she developed cardiogenic shock caused by advanced atrioventricular block. Laboratory tests revealed increased myocardium enzymes, and ultrasonic cardiography demonstrated mild thickening of the left ventricular wall. She was diagnosed with myocarditis and successfully treated using prednisolone. Myocarditis after allogeneic stem cell transplantation is a rare but potentially fatal complication. However, it is important for physicians to be aware of this complication because all of the symptoms may be reversed with immunosuppressive treatment.